Unification of Calculating the Performance of Vehicles and Transport-Technological Facilities - Maistrenko, Nikolay A.; Uvarov, Viktor P.; Levshin, Aleksandr G.; Khort, Dmitriy O.; Vorotnikova, Olesya S. (Inženernye tehnologii i sistemy, 2020)
Introduction. In agricultural production during transportation of goods it is accepted to allocate transport and transport-technological processes with the corresponding methods of rationing works. The peculiarity of the processes is the sequential execution of cyclic operations, providing transportation of technological material to the destination directly or with preliminary collection (subsequent distribution) on the field. At the same time, if the goods are moved directly between points, excluding technological (field) operations, this process can be considered a purely transport one, a special case of the transport and technological process. In this regard, it is proposed to consider this process as a component of the transport and technological process, which in turn requires correcting the applied methods for setting performance standards. The aim of the study is to develop a mathematical model and algorithm for standardizing the calculation of the performance of different vehicles and transport and technological facilities through formulating the dependence of the performance components on the power of the said facilities as their main classifier. Materials and Methods. The performance standards were identified by the extrapolation, interpolation or approximation methods based on their estimated performance. The classical method of differentiating functions was used to find the extrema. Результаты исследования.At length of fertilizer transportation by direct-flow technology LГ = 9 km and application dose U = 0.06 kg/m2, the following values of transport and technological facilities performance have been obtained: a) for vehicles to deliver fertilizers to fertilizer storehouses by Ural-432065 truck (body) W = 9.1 t/h, W = 6.3 t/h for tractor with MTZ-82 trailer. 1+2PTS-6; b) for transport and technological facilities to transport and distribute fertilizers by Ural-432065 (Amazone spreader) W = 5.5 t/h, W = 3.9 t/h for tractor with MTZ-82.1+RUM-6 trailer. Discussion and Conclusion. Based on the analysis of methods, the authors have made the case for the unification of calculating the standardized volumes of works, choice of composition, and comparison of the effectiveness of using vehicles, if they are used as transport and transport-technological facilities. A mathematical model and algorithm for a uniform calculation of the performance of different transport and technological facilities are presented. The way to determine the approximate rate of generation of funds that do not have standard indicators of work. The explanation of the innovations is accompanied by a formula device, which is based on the conclusion of the dependencies of out- and in-cycle components of the shift time balance on the engine power of the mobile device. The block diagram of the algorithm to calculate performance standards for vehicles is illustrated. The implementation of the algorithm is given by the example of using a specialized vehicle for transport and transport-technological operations.